O papel dos espaços educativos na formação inicial de professores de ciências/biologia : um olhar sobre o estágio supervisionado - Cabral, Hiléia Monteiro Maciel (2021)
There are many changes that undergraduate courses have undergone in recent decades. Thus, this study aimed to understand how educational spaces (museums, parks, squares) are addressed in the Licentiate Degree in Biological Sciences at Escola Normal Superior (ENS/UEA) so that it can contribute to the subjects Supervised Internship and in the formative process of the future Science/Biology teacher. For this, the data were collected through twenty semi-structured interviews, twenty teaching plans of the disciplines of supervised internship, fifteen internship report of the undergraduates, in the period from 2018/01 to 2019/02 and, finally, the Pedagogical Project of the Course (PPC). Data were analyzed in the light of Textual Discursive Analysis (ATD), which is divided into three stages: unitarization, categorization and construction of the metatext. In the unitarization process, 137 meaning units were generated, which were contextualized and inferred, producing a total of 48 purified meaning units. For the categorization step, these 48 contextualized and inferred units of meaning were grouped and compared to each other in an exhaustive way, generating six categories (three initial, two intermediate and one final category) which are: obtained i) Some subjects, such as Ecology, develop classes in educational spaces; ii) Confused ideas about educational spaces; iii) The breadth of the internship discipline beyond the classroom; iv) The supervised internship and its relationship with educational spaces; v) The educational spaces and their importance for the training of the licentiate; vi) It is a great challenge for the teacher to carry out activities in different spaces. These six categories served as a central element for the elaboration of the metatext (third phase of ATD) called: Educational spaces and supervised internship: extrapolating the walls of the school. These new understandings of this study revealed three important and striking points that we highlighted in this thesis: a) a theoretical significance: the reconfiguration of the internship disciplines of the Escola Normal Superior, which currently have four, now moving to three disciplines: the first in teaching Natural Sciences, in elementary schools; the second to be carried out in educational spaces, based on projects such as environmental education, etc; and the third in Biology teaching, in high schools, given that the supervised curricular internship is a privileged moment of contact with the school reality, when undergraduates experience important aspects of pedagogical practice, which can be carried out in different educational spaces. b) A practical significance: the creation of a discipline on educational spaces with 120 hours to be held in places such as the Science Forest, the Amazon Museum (MUSA), the Jungle War Instruction Center (CIGS), the Seringal Museum, etc organized in face-to-face theoretical-practical modules and non-face-to-face activity modules with the aim of aggregating knowledge and revealing the importance of these spaces for the formation of Science/Biology teachers. We believe that this proposal can also serve as a model for any other Licentiate course that has an interest in practice (in different spaces) as a curricular component. c) A scientific novelty, that is, the revelation of a differentiated alternative for the supervised Internship activities in educational spaces, since conventionally it is only dealt with in formal educational spaces.